2020
DOI: 10.3389/fbioe.2019.00438
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PGRMC1 as a Candidate Oncogene for Head and Neck Cancers and Its Involvement in Metabolic Activities

Abstract: Progesterone Receptor Membrane Component 1 (PGRMC1/Sigma-2 receptor) is located on chromosome Xq21 and encodes a haem-containing protein that interacts with epidermal growth factor receptor (EGFR) and cytochromes P450, with function in tumor proliferation and chemoresistance. Although the over-expression of PGRMC1 reported in many different types of human cancers, systematic analysis of its oncogenic role of PGRMC1 has not been performed for any cancer. In this work, we analyzed the transcriptomics, genomics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…One example is the role of Pgrmc1 in breast cancer [ 32 , 33 ], as Pgrmc1 has been recently identified to play important roles in the survival duration and metastasis of breast cancers in a murine PyMT model [ 34 ]. Pgrmc1 is also known to be highly expressed in various types of cancers and associated with the survival rate of patients with head and neck cancer [ 35 ], lung and ovarian cancers [ 36 ], and breast cancer [ 32 , 33 ]. Of note, PGRMC1 exists in protein complexes including EGFR and modulates its expression levels in multiple cancer cell lines (breast, lung, colon cancers) and affects their proliferation and chemoresistance [ 20 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…One example is the role of Pgrmc1 in breast cancer [ 32 , 33 ], as Pgrmc1 has been recently identified to play important roles in the survival duration and metastasis of breast cancers in a murine PyMT model [ 34 ]. Pgrmc1 is also known to be highly expressed in various types of cancers and associated with the survival rate of patients with head and neck cancer [ 35 ], lung and ovarian cancers [ 36 ], and breast cancer [ 32 , 33 ]. Of note, PGRMC1 exists in protein complexes including EGFR and modulates its expression levels in multiple cancer cell lines (breast, lung, colon cancers) and affects their proliferation and chemoresistance [ 20 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant expression of PGRMC1 at both transcript and protein levels have been reported in multiple types of cancer, including breast (Neubauer et al, 2013;Li et al, 2019), ovarian (Peluso et al, 2008;Mir et al, 2012), as well as head and neck cancer (Zhao and Ruan, 2019). PGRMC1 may regulate the proliferation and progression of breast cancer cells, potentially by altering lipid metabolism and by activating key oncogenic signaling pathways, such as ERα expression and activation, as well as EGFR signaling (Asperger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ARF4 may play key roles in HO development. PGRMC1/Sigma-2 receptor is confirmed to play key roles in the function of tumor proliferation (such as breast tumors, lung adenocarcinoma cells, and ovarian cancer) and chemoresistance (44)(45)(46)(47). Recent research showed that PGRMC1 significantly suppresses the hydrogen peroxide-induced oxidative stress response in full-thickness fetal membrane explants and chorion cells (48).…”
Section: Discussionmentioning
confidence: 99%